The psychological costs of unsustainable housing commitments - Mark P. Taylor; David J. Pevalin; Jennifer Todd (University of Essex, Institute for Social and Economic Research (ISER), 2006)
We explore the impact of unsustainable housing commitments on psychological well-being using data from the British Household Panel Survey. We test the hypotheses that (i) housing payment problems, housing arrears and the threat of eviction and repossession have adverse impacts on heads of households psychological well-being over and above those caused by financial hardship and (ii) these impacts are larger for homeowners than for tenants. Our results indicate that for both men and women persistent housing payment problems have significant psychological costs. We find that for men entering arrears and the imminent threat of home loss has deleterious impacts on psychological health. The sizes of these effects are independent of and larger in magnitude to those associated with financial hardship more generally. We also find housing payment arrears have a significantly greater impact on psychological wellbeing among homeowners than tenants.
Keywords: 330